Short-term outcomes in patients with branch retinal vein occlusion who received intravitreal aflibercept with or without intravitreal ranibizumab - Sakanishi Y (Dove Medical Press, 2017)
Yoshihito Sakanishi, Ayumi Usui-Ouchi, Kazunori Tamaki, Keitaro Mashimo, Rei Ito, Nobuyuki Ebihara Department of Ophthalmology, Juntendo University Urayasu Hospital, Urayasu City, Chiba, Japan Purpose: The purpose of this study was to determine the short-term outcomes for patients who received intravitreal aflibercept (IVA) with or without intravitreal ranibizumab (IVR) for macular edema (ME) due to branch retinal vein occlusion (BRVO). Patients and methods: Patients received IVA for ME due to BRVO. Patients who initially received IVA were defined as the treatment-naïve group and those who were switched from IVR to IVA after ME recurrence were defined as the switching group. Patient outcomes were examined at 1 week and 1 month postinjection. Results: Both groups comprised 27 eyes from 27 patients. There was a significant decrease in central macular thickness (CMT) at 1 week and 1 month postinjection in both groups. There was also a significant improvement in best-corrected visual acuity (BCVA) at 1 week and 1 month postinjection in the treatment-naïve group and 1 month in the switching group. Younger age was associated with a good BCVA at 1 month postinjection in the switching group, and the absence of epiretinal membrane was associated with a reduction in CMT at 1 month postinjection in the switching group. Conclusion: IVA is temporarily effective for treating ME due to BRVO regardless of a history of IVR use. Keywords: BRVO, IVR, IVA, switch